Inflammatory bowel disease in the coronavirus (COVID-19) pandemic. (2nd May 2020) - Ma, Sara; Rook, Lisa; Galdas, Paul
Abstract : This article aims to inform how specialist inflammatory bowel disease (IBD) nurses can protect IBD patients through the novel coronavirus (COVID-19) pandemic